PERSPEKTIF MAHASISWA PGMI SEBAGAI CALON GURU MI TERHADAP EVALUASI PSIKOMOTORIK DALAM PEMBELAJARAN PENDIDIKAN ISLAM - Muthia Salsabila; Allisya Nurfitria; Aulia Ananda Pratiwi; Asep Ediana Latip (STKIP Subang, 2025)
This study aims to analyze the perspective of PGMI students as prospective MI teachers towards the implementation of psychomotor evaluation in Islamic Education learning. Psychomotor evaluation is understood as an assessment of students' religious practice skills, ranging from the accuracy of worship movements to the ability to apply religious teachings in real actions. This study uses a survey method with instruments in the form of 24 statements developed based on eight aspects of psychomotor evaluation. A total of 33 PGMI students in the third semester became research respondents, while the instrument validation test was carried out by students outside the sample to ensure the clarity of the items and the suitability of the indicators. The results of the study show that the majority of students have a good understanding of the concept and urgency of psychomotor evaluation, and view the method of direct observation and the use of rubrics as an effective and relevant approach in assessing religious practice skills. Students also show a fairly high level of readiness in implementing psychomotor evaluation, although they are still aware of technical constraints, time constraints, and the need for standardized instruments and advanced training. Overall, this study shows that PGMI students are at a positive stage of readiness in implementing psychomotor evaluation, but still need to strengthen their competencies so that the assessment of religious practices in Madrasah Ibtidaiyah can be carried out objectively, systematically, and contextually.